Creative imagination and creativity - Di Gregori, Cristina (2018)
In the last decades the idea of creativity has gained increasing interest in the field of philosophy, cognitive sciences, sociology, etc. and there have been renewed contributions regarding the classic idea of creativity. We consider that the contribution of classic pragmatism deserves special mention-particularly in the works of Charles S. Peirce and John Dewey. In this article, we are going to refer exclusively to the Deweyan treatment of this idea. We will expose some consequences of his position-as we interpret it. In effect, we are going to sustain the Dewey moves away from classic demands according to which a creative product involves, neccessarily, a radical transformation of human life, according to the idea of degrees of creativiy; that this Deweyan theory constitutes an interesnting insight for promoting the creative attitude; that the creative process retains the same structure in all cases-science and art, for example-and that creativity is now an intrinsic potentiality of human beings-which may be realiized or not. Finally, we consider the relevance of some Deweyan theses for nowadays positions, as in the case of the cognitive psychologist Robert Weisberg, emphasizing, their coincidences and disagreements.